2009
DOI: 10.1038/ajg.2009.524
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Small Intestinal Microbiota and Identification of Rod-Shaped Bacteria Associated With Childhood Celiac Disease

Abstract: Rod-shaped bacteria, probably of the indicated species, constituted a significant fraction of the proximal small intestine microbiota in children born during the Swedish CD epidemic and may have been an important risk factor for CD contributing to the fourfold increase in disease incidence in children below 2 years of age during that time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
111
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(127 citation statements)
references
References 28 publications
10
111
0
6
Order By: Relevance
“…9 It has been proposed that some immunologically relevant CD-associated alleles-including the SH2B3 rs3184504*A allele, which plays a protective role against bacterial infection-may have undergone positive selection rather recently. 8 This finding, along with those in other recent studies of the role of infections 10 and intestinal indigenous microflora composition 11,12 in CD, show that immune reactions to gluten are strongly influenced by changes in the intestinal microbiome.…”
supporting
confidence: 78%
“…9 It has been proposed that some immunologically relevant CD-associated alleles-including the SH2B3 rs3184504*A allele, which plays a protective role against bacterial infection-may have undergone positive selection rather recently. 8 This finding, along with those in other recent studies of the role of infections 10 and intestinal indigenous microflora composition 11,12 in CD, show that immune reactions to gluten are strongly influenced by changes in the intestinal microbiome.…”
supporting
confidence: 78%
“…In recent T1D and CD investigations, intestinal microbiota have received attention as possible modulators of disease development. [27][28][29][30] However, one could ask whether the detection of serum antibodies against antigens of a particular commensal bacteria reflects its presence and involvement in immune reactions at the intestinal level. Although it is possible that we detected antibodies induced by antigens that originated from other microorganisms, we are still confident that a portion of the detected antibodies was directed against B. adolescentis itself or other Bifidobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] In experimentally induced diabetes in rats or mice, changes in intestinal permeability are also detected before the onset of diabetes; increased intestinal permeability in these cases has been shown to be dependent on increased zonulin expression, which regulates tight junctions in the intestinal mucosa. [25][26][27] Additionally, mucosal biopsy, fecal microbiota and serological studies have indicated that the composition of intestinal microbiota may influence the immune mechanisms that participate in the development of CD 28,29 and T1D. 27,29,30 Consistent with these studies, recent investigations have stressed the importance of Bifidobacteria species and strains in the modulation of immune reactivity at the intestinal mucosa level.…”
Section: Introductionmentioning
confidence: 92%
“…Carcinoembryonic antigen-related cell adhesion molecule (CEACAM), one member of CEA gene family, belongs to the immunoglobulin superfamily of adhesion molecule anchoring at the cell membrane. CEACAM1 is considered to be anti-oncogene, but expressing in lung cancer, especially in lung adenocarcinoma, can promote tumor angiogenesis (Ou et al, 2009). CEACAM5 and CEACAM6 are considered to be oncogene.…”
Section: Discussionmentioning
confidence: 99%